2014
DOI: 10.5551/jat.23259
|View full text |Cite
|
Sign up to set email alerts
|

A Low Serum Free Triiodothyronine Level is Associated with Epicardial Adipose Tissue in Peritoneal Dialysis Patients

Abstract: Aim: Cardiovascular disease is a major cause of mortality in dialysis patients. Epicardial adipose tissue (EAT) has been proposed as a cardiovascular risk marker in this population. Subclinical hypothyroidism and low free triiodothyronine (fT3) levels are associated with EAT in patients without chronic renal failure. The aim of this study was to investigate the relationship between EAT and low free T3 levels in peritoneal dialysis (PD) patients. Methods: A total of 125 prevalent PD patients were enrolled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Excess visceral adiposity is frequently accompanied by ectopic fat accumulation such as fat accumulation in the liver, heart, and blood vessels [ 36 ]. It has been demonstrated that endothelial function is impaired in patients with non-alcoholic fatty liver disease [ 37 ], patients with increased epicardial adipose tissue [ 38 , 39 ], and subjects with increased perivascular adipose tissue [ 40 ]. It has been suggested that ectopic fat deposition is associated with insulin resistance and an increased risk of cardiovascular complications [ 41 , 42 ].…”
Section: Visceral Adiposity and Endothelial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess visceral adiposity is frequently accompanied by ectopic fat accumulation such as fat accumulation in the liver, heart, and blood vessels [ 36 ]. It has been demonstrated that endothelial function is impaired in patients with non-alcoholic fatty liver disease [ 37 ], patients with increased epicardial adipose tissue [ 38 , 39 ], and subjects with increased perivascular adipose tissue [ 40 ]. It has been suggested that ectopic fat deposition is associated with insulin resistance and an increased risk of cardiovascular complications [ 41 , 42 ].…”
Section: Visceral Adiposity and Endothelial Functionmentioning
confidence: 99%
“…Adipose tissue transplant studies in mice demonstrated that perivascular adipose tissue harvested from obese mice promotes inflammation and endothelial dysfunction in recipient mice [ 49 , 50 ]. In addition, a number of clinical studies have suggested links between ectopic fat deposition and endothelial function [ 38 , 39 , 40 , 42 , 51 , 52 , 53 ]. The thickness of epicardial fat has been shown to be associated with endothelial dysfunction [ 38 , 52 ].…”
Section: Visceral Adiposity and Endothelial Functionmentioning
confidence: 99%
“…Manes and his colleagues, in their study of Left ventricular geometric patterns and cardiac function in patients with chronic renal failure undergoing hemodialysis also found that diastolic dysfunction was found in 87% of patients. The relatively higher percentage in their study may be explained by their enrollment of diabetic patients in their study [70].…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have reported that EAT potentially causes local inflammation and may be seen as a marker for the risk of cardiovascular disease ( 16 ). Studies have indicated that EAT is an important risk factor for atherosclerotic diseases and metabolic syndrome ( 17 , 18 ). The correlation between EAT and CAD has been previously reported; however, it is controversial whether EAT may be regarded as a marker to predict the occurrence and development of CAD ( 19-21 ).…”
Section: Introductionmentioning
confidence: 99%